2015
DOI: 10.1016/j.jiph.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the International Nosocomial Infection Control Consortium (INICC) multicenter, multidimensional hand hygiene approach in two cities of India

Abstract: The fundamental tool for preventing and controlling healthcare-acquired infections is hand hygiene (HH). Nonetheless, adherence to HH guidelines is often low. Our goal was to assess the effect of the International Nosocomial Infection Control Consortium (INICC) Multidimensional Hand Hygiene Approach (IMHHA) in three intensive care units of three INICC member hospitals in two cities of India and to analyze the predictors of compliance with HH. From August 2004 to July 2011, we carried out an observational, pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
1
23
1
Order By: Relevance
“…In low-income and middle-income countries, HH compliance was averaged 22·4% before multimodal intervention [ 11 ]. Hand hygiene compliance was much lower in the present study compared to post- multimodal intervention studies from India (82%) [ 15 ], Kuwait (61.4%) [ 25 ], and Colombia (77%) [ 26 ]. The possible reason for low compliance in our study might be due to the WHO’s multimodal HH improvement strategy which was not implemented.…”
Section: Discussioncontrasting
confidence: 73%
“…In low-income and middle-income countries, HH compliance was averaged 22·4% before multimodal intervention [ 11 ]. Hand hygiene compliance was much lower in the present study compared to post- multimodal intervention studies from India (82%) [ 15 ], Kuwait (61.4%) [ 25 ], and Colombia (77%) [ 26 ]. The possible reason for low compliance in our study might be due to the WHO’s multimodal HH improvement strategy which was not implemented.…”
Section: Discussioncontrasting
confidence: 73%
“…An example is the International Nosocomial Infection Control Consortium (INICC) Multidimensional Hand Hygiene Approach (IMHHA), which includes administrative support, availability of supplies, education and training, reminders, process surveillance, and performance feedback. Previous studies have reported significant improvement in adherence to hand hygiene with the implementation of the IMHHA in ICUs in various countries [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 95%
“…A prospective observational study involving 99 ICUs in 19 resource-limited countries demonstrated a significant 23.1% overall increase in hand hygiene compliance after implementation of a multidimensional hand hygiene program involving administrative support, supply availability, education and training, workplace reminders, process surveillance, and performance feedback [84]. These findings have been replicated in geographically diverse locations including India [85], China [86], and Mexico [87]. A prospective study in six Colombian ICUs demonstrated a significant reduction (12.7% annually during the 4-year study period) in central line-associated bloodstream infections after introduction of a targeted hand hygiene program that included installation of alcohol-based hand rub dispensers adjacent to each ICU bed and regular feedback to healthcare workers [88].…”
Section: Hygienementioning
confidence: 99%